2011
DOI: 10.1002/jmv.22214
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV, syphilis, and hepatitis C virus in the general population of the Liangshan Prefecture, Sichuan Province, China

Abstract: This study aimed at understanding the HIV prevalence, distribution of HIV risk factors and whether the HIV has spread from high-risk groups to the general population in the Yanyuan and Muli counties, Liangshan Prefecture, Sichuan Province, China. A multistage probability method was used to select a representative sample of villages in each county, with stratification by risk employed in the sampling for the Yanyuan county. A real-name registration and confidential method were adopted to collect the information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…These are both higher than the divorced/widowed group (HIV: 5.6%, HCV: 6.1%). Combined with the results of multiple sexual partners (male: 29.9%, female: 17.1%), which were higher than in other, low HIV prevalence regions [25], we think that having multiple sexual partners is a very important risk factor for HIV infection. In contrast to the total study population, we found that education was related to HIV infection, but knowledge was not.…”
Section: Discussionmentioning
confidence: 58%
“…These are both higher than the divorced/widowed group (HIV: 5.6%, HCV: 6.1%). Combined with the results of multiple sexual partners (male: 29.9%, female: 17.1%), which were higher than in other, low HIV prevalence regions [25], we think that having multiple sexual partners is a very important risk factor for HIV infection. In contrast to the total study population, we found that education was related to HIV infection, but knowledge was not.…”
Section: Discussionmentioning
confidence: 58%
“…The first case of HIV was observed among drug users in eastern M county in 1995. From there, the HIV epidemic spread to all 16 counties and a city [38]. In general, male drug users were found to engage in more risky behavior than female drug users, such as sharing syringes.…”
Section: Discussionmentioning
confidence: 99%
“…The Yi ethnic minority still maintains traditional social norms and values, including arranged marriage between individuals of the same social status and acceptance of casual sex. Condom use is infrequent among Yi [38], [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AIDSrelated deaths increased by 66% in this region compared to a worldwide fall of 35% between 2005 and 2013 (13). Similarly, a very low HIV prevalence has been reported in the general population of Sichuan, China (14). The prevalence of the infection in Yanyuan was reported as low as 0.06% and in Muli no one was found to be HIV positive.…”
Section: Discussionmentioning
confidence: 79%